The Effect of Using Digital-Based Learning Media on Student Competence: An Observational Study of Senior High School Students in Jambi City, Indonesia - Pratama, Aditya; Arpizal; Novia Sri Dwijayanti (Arkus, 2024)
Digital transformation in education has encouraged the use of digital-based learning media (MPBD) at various levels, including senior high school. This study aims to analyze the effect of using MPBD on the competency of senior high school students in Jambi City, Indonesia. This research uses an observational design with a quantitative approach. The sample consisted of 350 senior high school students in Jambi City who were randomly selected in stages. Data was collected through questionnaires, class observations, and document analysis (report scores). Data analysis was carried out using multiple linear regression. The research results show that the use of MPBD has a positive and significant effect on student competence (p < 0.05). Factors such as intensity of use of MPBD, quality of MPBD, and teacher support also contribute significantly to increasing competency. The use of MPBD that is well integrated in the learning process can increase the competence of senior high school students. Improving the quality of MPBD, teacher training and infrastructure support is needed to optimize the use of MPBD in education.